Use completion of squares to determine the solution of 3x^2 + 6x + 2 = 0

### 1 Answer | Add Yours

The equation 3x^2 + 6x + 2 = 0 has to be solved.

3x^2 + 6x + 2 = 0

=> `(sqrt3*x)^2 + 2*sqrt3*sqrt 3*x + 2 = 0`

=> `(sqrt3*x)^2 + 2*sqrt3*sqrt 3*x + (sqrt 3)^2 + 2 = (sqrt 3)^2`

=> `(sqrt3*x)^2 + 2*sqrt3*sqrt 3*x + (sqrt 3)^2 = 3 - 2`

=> `(sqrt 3*x + sqrt 3)^2 = 1`

=> `sqrt 3*x + sqrt 3 = +-1`

=> `x = (+-1 - sqrt 3)/sqrt 3`

=> `x = +-1/sqrt 3 - 1`

**The roots of `3x^2 + 6x + 2 = 0` are `+-1/sqrt 3 - 1` **

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes